MAMS: a new AMS facility at the Curt-Engelhorn-Centre for Achaeometry, Mannheim, Germany - Kromer, Bernd; Lindauer, Susanne; Synal, Hans-Arno; Wacker, Lukas (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2013)
A new AMS lab has been established at the Curt-Engelhorn-Centre for Achaeometry, Mannheim, Germany, based on the compact MICADAS (Mini Carbon Dating System). After 1year of operation we can demonstrate the high stability and ease of operation of the MICADAS concept. We are confident that we can obtain a precision of modern samples, e.g. for carbon cycle studies, at the 2permille level. The 200kV design results in a comparatively low initial budget and economic operational costs.
Available online 21 January 2012
Gesehen am 31.03.2021